Question #6b55e
2 Answers
Aug 23, 2017
I will assume that we want to find
Explanation:
Use
And the chain rule again
So,
= cot^2x (2tanxsec^2x)
= 2cotxsec^2x
= 2cscxsecx
Aug 24, 2017
Explanation:
We can also simplify the function using the following logarithm rules:
log(a^b)=blog(a) log(a/b)=log(a)-log(b)
So:
y=ln(tan^2x)=2ln(tanx)=2ln(sinx/cosx)=2ln(sinx)-2ln(cosx)
Taking the derivative, we need to remember that
dy/dx=2/sinx(d/dxsinx)-2/cosx(d/dxcosx)
dy/dx=(2cosx)/sinx+(2sinx)/cosx=(2(cos^2x+sin^2x))/(sinxcosx)
Since
dy/dx=2cscxsecx